(untitled) (Research, Society and Development, 2024)
Objectives: to describe the needs for guidance from family members and caregivers of the elderly in palliative care in the context of hospital discharge to the home. Method: a descriptive study with a qualitative approach. The research participants included family members and caregivers of patients in palliative care with indication and / or probability of indicating discharge from hospital to the home, aged 18 years or older. Results: concerns and feelings: anxiety; relief; concern about changing the routine and how care will be divided between other family members and caregivers and the fear of the patient dying at home. Doubts about the demands of home care were highlighted: oxygen therapy, care for pressure injuries and food. Conclusion: It is necessary to implement interventions that improve, among other issues, communication between professionals and the user in the preparation and education for care at home, with the provision of community support networks and early treatment of mourning.